Murder house - Patterson, James, 1947-; Ellis, David, 1967- (New York : Little, Brown and Company, 2015)
Returning to the luxurious Hamptons of her youth to investigate the murders of a Hollywood power broker and his mistress, detective Jenna Murphy uncovers links between the case and a series of unsolved killings.
Keywords: Women detectives -- Fiction; Murder -- Investigation -- Fiction; Mansions -- New York (State) -- Hamptons -- Fiction; Women detectives -- Fiction; Homicide -- Fiction; Criminal investigation -- Fiction; Mansions -- Hamptons (N.Y.) -- Fiction; Hamptons (N.Y.) -- Fiction; Hamptons (N.Y.) -- Fiction; Suspense fiction; Suspense fiction